Hubungan Tingkat Kecemasan Dengan Kualitas Tidur Pasien Covid-19 di RSUD Prof. Dr. W. Z. Johannes Kupang - latuperissa, alfonso jacobi; Lada, Christine Olly; Tallo Manafe, Derri Riskiyanti; Wungouw, Herman P.L. (Cendana Medical Journal, 2026)
Abstract Coronavirus Disease 2019 (COVID-19) is a contagious infectious disease that attacks the respiratory system caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). On March 11, 2020, WHO declared COVID-19 a pandemic and until October 14, 2022, 620 million confirmed cases, and of this 6 million people died (3). Generally, COVID-19 patients isolated in hospitals have higher levels of anxiety and somatization symptoms because patients think negative things so that patients become pessimistic. The immune system of COVID-19 patients is a major factor in the healing process. The anxiety experienced by the patient causes a lack of rest and a decrease in the quality of the patient's sleep (12). The condition of the COVID-19 pandemic tends to have a negative impact on several factors that affect a person's sleep quality so that researchers are interested in further researching the relationship between anxiety levels and sleep quality, especially in COVID-19 patients at Hospital Prof. Dr. W Z Johannes Kupang. This study is a retrospective analytic study using a cross-sectional approach. The sampling technique in this study used a purposive sampling technique with the aim of taking samples according to the inclusion criteria. The sample in this study was determined using a formula to test the correlation coefficient so that a sample size of 50 respondents was obtained. Where the analysis used in this study uses the Spearman rank test. From 50 respondents, 27 respondents (54%) experienced moderate anxiety and 42 respondents (84%) had poor sleep quality. Spearman rank test results obtained p = 0.000 and the value of r = 0.546.There is a significant relationship between anxiety levels and sleep quality of COVID-19 patients at Hospital Prof. Dr. W Z Johannes Kupang. Keywords: COVID-19, Anxiety, Sleep Quality, COVID-19 Patients